Association of Attention-Deficit/Hyperactivity Disorder With E-Cigarette Use - Xu, Guifeng; Snetselaar, Linda G.; Strathearn, Lane; Ryckman, Kelli; Nothwehr, Faryle; Torner, James (American journal of preventive medicine, 2021)
E-cigarette use in young people has emerged as a public health concern in the U.S. Previous studies have shown that individuals with attention-deficit/hyperactivity disorder are more likely to use conventional cigarettes. However, little is known about their use of E-cigarettes. This study examines the association of attention-deficit/hyperactivity disorder with E-cigarette and other tobacco product use among undergraduate and graduate students in the U.S. This study included data from 195,443 U.S. undergraduate and graduate students aged 18–39 years who participated in the National College Health Assessment surveys from spring 2017 to fall 2018. History of attention-deficit/hyperactivity disorder diagnosis and current use of conventional cigarettes, E-cigarettes, and other tobacco products were ascertained by questionnaires. Logistic regression models estimated the ORs and 99% CIs of use of conventional cigarettes, E-cigarettes, and other tobacco products according to attention-deficit/hyperactivity disorder history. Among the 195,443 students, 16,800 (8.35%) were current conventional cigarette users and 15,863 (7.89%) were current E-cigarette users; 16,283 (8.10%) had a history of attention-deficit/hyperactivity disorder diagnosis. After adjustment for demographics, socioeconomics, lifestyle factors, BMI, anxiety, and depression, the OR of E-cigarette use among participants with attention-deficit/hyperactivity disorder, compared with those without attention-deficit/hyperactivity disorder, was 1.72 (99% CI=1.60, 1.85), which was comparable to the magnitude of associations for other tobacco products. Among U.S. undergraduate and graduate students, there is a significant association between attention-deficit/hyperactivity disorder diagnosis and current use of E-cigarettes. Health consequences of E-cigarette use among individuals with an attention-deficit/hyperactivity disorder diagnosis warrant further investigation.